Perinatal gene delivery to the CNS. (April 2011) - Rahim, Ahad A; Buckley, Suzanne MK; Chan, Jerry KY; Peebles, Donald M; Waddington, Simon N
The relative inaccessibility of the brain compared with other major organs, the highly regulated transfer of molecules across the blood––brain barrier and the limited capacity of neurons to regenerate, make efficient gene delivery to the CNS both challenging and imperative. Perinatal gene delivery to the CNS represents a powerful tool for the investigation of genes in development and disease. However, it may also hold immense therapeutic value for neonatal lethal neurodegenerative diseases for which no treatment is available. This article will focus on the use of perinatal gene delivery as a research tool and the potential it has to develop into a realistic therapy that can be translated to the clinic.